Kompetensi Tenaga Administrasi Pengaruh Kompetensi Terhadap Kinerja Tenaga Administrasi Sekolah di UPT SMA Negeri 1 Wajo: Kompetensi Tenaga Administrasi Sekolah - Muhammad Arafah; Muhammad Nasir; Evita Lestari; Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the finding that some school administrative staff have not been fully able to complete their tasks optimally. This condition is thought to be caused by low levels of competence in several important aspects, such as technical, managerial, and interpersonal skills. Based on this, this study was conducted to analyze the effect of competence on the performance of school administrative staff. This study uses a quantitative approach with a survey method. The subjects in this study were all administrative staff of UPT SMA Negeri 1 Wajo, totaling 22 people. Data collection was carried out through a closed questionnaire with a Likert scale. Data analysis was carried out descriptively and inferentially using a simple linear regression test with the help of the SPSS version 30.0 program. The results of the study showed that the competence of administrative staff was in the